Penggunaan Model Problem Solving Dalam Menyelesaikan Soal Cerita Matematika Di SDN 211/Ix Mendalo Darat - Juhairiah Juhairiah (Universitas Batanghari Jambi, 2020)
This study presents the problem that is solving math story question is a difficulty for students so the teacher uses a problem solving model and students will find it easier to understand the meaning of the story question and be able to solve them. The research design is qualitative and descriptive approach. The subjects in this study were the principal, student guardians of grade 4 (mathematics teacher), and students. Data collection techniques were in the form of interviews, observation, and documentation. The results of this study indicate that by planning, implementing, evaluating the use of a good problem solving model will be able to solve problems, with the obstacles and efforts will be get a good result.